Alteration of Hadith Functions in TikTok Social Media - Miski Miski; Putri Ghoida’ Habibillah (Jurnal Living Hadis, 2022)
This article categorized as a netnographic study that refers to uploads on the TikTok platform with various kinds of discussions in the name of the prophet's Hadits or Sunnah. Therefore, the three questions proposed are: 1) how does the Hadits in the TikTok experience a change in function? 2) How efficient is TikTok in conveying the prophet’s teachings? 3) What are the motivations that trigger users to upload content based on the prophet's Hadits? By conducting the content analysis of this study, it could be conclude that: 1) the Hadits which have spread on TikTok have changed their function, which originally served as a bayan, have now become certain tools for certain purposes, 2) in that narrow space, the prophet's Hadits could not be delivered comprehensively and completely because the facilities provided by TikTok could not accommodate all explanations so that siltation appears, 3) the wide range and the availability of features that support the transaction process contribute the creation of a massive commodification process. In addition, this paper also reviews the transfiguration of pretensions which are implied in the TikTok circulation chain. Some of these things denoted that the hadits circulating on the TikTok have problems that could not be ignored.